"I Feel Like I Have Lost Part Of My Identity" - A Qualitative Study Exploring The Impact Of Chronic Ankle Instability - Anders Mohrsen; Thomas Sørensen; Henrik Lund; Steven Zartov Rasmussen; Asger Jensen; Katrine Bruun Skov; Michael Skovdal Rathleff (International Journal of Sports Physical Therapy)
# Introduction